2016
DOI: 10.1002/1873-3468.12169
|View full text |Cite
|
Sign up to set email alerts
|

miR‐375 negatively regulates porcine preadipocyte differentiation by targeting BMPR2

Abstract: The differentiation of preadipocytes into adipose tissues is tightly regulated by various factors including miRNAs and cytokines. In this study, taking advantage of isolated porcine primary preadipocytes, we showed that ectopic expression of miR-375 could change preadipocyte differentiation. In addition, bone morphogenetic protein receptor 2 (BMPR2) was identified as a direct target of miR-375. Silencing BMPR2 had the same inhibition effects as overexpressing miR-375 on the preadipocyte differentiation. Togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Therefore, in light of the presented experimental results, we speculate that in bovine CCs cultured in vitro, the GDF9/BMP15 heterodimer may bind to BMPR2-ALK7-ALK6 to form a receptor complex and induce SMAD2/3 phosphorylation and thereby regulate the expression of CC expansion-associated genes (PTX3/HAS2/PTGS2). BMPR2 is a target gene of miR-375 [29]. Thus, miR-375 regulates the elevation and reduction of BMPR2 expression and thereby modulates the SMAD2/3 pathway involving the GDF9/BMP15 heterodimer, affecting the proliferation and apoptosis of bovine CCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in light of the presented experimental results, we speculate that in bovine CCs cultured in vitro, the GDF9/BMP15 heterodimer may bind to BMPR2-ALK7-ALK6 to form a receptor complex and induce SMAD2/3 phosphorylation and thereby regulate the expression of CC expansion-associated genes (PTX3/HAS2/PTGS2). BMPR2 is a target gene of miR-375 [29]. Thus, miR-375 regulates the elevation and reduction of BMPR2 expression and thereby modulates the SMAD2/3 pathway involving the GDF9/BMP15 heterodimer, affecting the proliferation and apoptosis of bovine CCs.…”
Section: Discussionmentioning
confidence: 99%
“…While the synergy interaction of BMP15/GDF9 or GDF9 alone is known to activate SMAD2/3 signaling, the mechanism and the involved genes by which BMP15/GDF9 produces an effect in bovine CCs remains unknown. Furthermore, our previous studies found that BMPR2 is a direct target of miR-375 in bovine cumulus cells [29]. While the individual or synergistic effect of BMP15/ GDF9 requires binding to BMPR2, the mechanism by which miR-375 regulate BMPR2 expression and thereby balance the effect of BMP15/GDF9 has yet to be determined.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, miR-375 is significantly downregulated in several types of tumors, and suppresses their proliferation by targeting some important genes, e.g., JAK2 , YAP1 , and PDK1 (Ding et al., 2010, Zhang et al., 2013, Zhou et al., 2014). Research has shown that miR-375 is a negative regulator of adipogenic differentiation by targeting bone morphogenetic protein receptor 2 (BMPR2) (Liu et al., 2016a). Osteoblastic and adipocytic lineages have alternative fates during development and aging, and increased adipogenesis correlates with decreased osteogenesis (Takada et al., 2009, Verma et al., 2002), which led us to speculate that miR-375 might play a role in the differentiation of stem cells toward osteogenic lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Id1, Id2 , and Id3 regulate HC formation during development by negatively regulating Atoh1 (Ozeki et al, 2005; Jones et al, 2006; Laine et al, 2010; Zhan et al, 2017). Tfdp1 encodes a TF that binds to the promoter regions of a number of genes whose products are involved in cell cycle regulation or in tumor proliferation (Vairapandi et al, 2002; Yasui et al, 2003; Liu S. et al, 2016; Lu et al, 2016). Bmpr2 encodes a member of the bone morphogenetic protein receptor family of transmembrane serine/threonine kinases that play important roles in stem cell differentiation (Zeng et al, 2012; Larabee et al, 2015; Ramos-Solano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%